Identification of vehicle rollover conditions and active roll control strategies [electronic resource] - Amrik Singh Phuman Singh, 1985- (2012)
Thesis (Sarjana Kejuruteraan (Mekanikal)) - Universiti Teknologi Malaysia, 2012